(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2024)
A pot experiment was carried out in the net house of the Department of Soil, Water and Environment, University of Dhaka. The aim of the study was to assess growth and yield performance of Neem seedlings with the different doses of organic and NPK fertilizers. Trichocompost (TC) was used as organic fertilizer. The treatments used in the experiment were: T1: Control (-OM and -NPK), T2: TC (10 ton/ha), T3: TC 5 ton/ha, T4: NPK 100% RDF, T5: NPK 80% RDF + TC 5 ton/h, T6: NPK 60% RDF + TC 5 ton/h, T7: NPK 40% RDF + TC 5 ton/h, T8: NPK 80% RDF + TC 10 ton/h, T9: NPK 60% RDF + TC 10 ton/h, T10: NPK 40% RDF + TC 10 ton/h. Pots were arranged in a Completely Randomized Design (CRD). Plant height and the number of leaves per plant were recorded at a 15-day interval. The tallest plant (78.87 cm) observed with the application of sole Trichocompost 5 ton/ha. Incremental dose of TC and inorganic fertilizer reduces the height of plant. The maximum no. of leaves ( 51.67) was found with NPK 60% RDF + TC 5 ton/h at the stage of 90 days and the next highest amount of leaves (44.67) with NPK 80% RDF + TC 10 ton/h at 90 days after. The lowest height (12.52 cm) and leaf number/plant (8.33) were recorded in control. Maximum fresh and dry weights (root, bark, and leaf) were 17.19 g/plant and 6.24 g/plant, respectively, found in T8: (NPK 80% RDF + TC 10 ton/h). The best growth performance of seedlings was observed in T8: NPK, 80% RDF, and TC 10 ton/h .The research indicated that there was no significant treatment difference on nutrient uptake by the neem seedlings. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 81-90